Profile of generation Z characteristics: Implications for contemporary educational approaches - Wajdi, Majid; Susanto, Budi; Sutiarso, M. Agus; Hadi, Wisman; Sumartana, I Made (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2024)
Generation Z, comprised of individuals born between the late 1990s and early 2010s, has become a subject of interest in discussions on social, cultural, and educational trends. Technological advancements and changes in social dynamics have significantly influenced the characteristics of this generation. This research aims to provide an in-depth understanding of Generation Z characteristics and explore how these traits can shape contemporary educational approaches. Thus, the study seeks to offer new insights to educators, curriculum planners, and educational policymakers. The research method involves a document study. It involves a document review conducted to detail the historical, social, and technological contexts that have shaped the identity of Generation Z. Data analysis reveals that Generation Z tends to have a digital orientation, engage in multitasking, exhibit high levels of creativity, and embrace inclusive values. They also demonstrate a significant interest in social engagement and environmental concerns. The implications of these findings on education highlight the need for responsive and innovative approaches to optimize the learning process. By understanding the characteristics of Generation Z, educators can design more effective and relevant teaching strategies. Educational approaches that focus on technology, engaging learning experiences, and the promotion of inclusive values can enhance the effectiveness of learning. Additionally, educators need to be aware that continuous adaptation to technological developments and social changes is key to creating a dynamic educational environment that aligns with the needs of Generation Z. The pedagogical implications of this research can serve as a foundation for curriculum development, teacher training, and educational policies that better align with the unique characteristics of Generation Z.